Cholesterol Accumulation as a Driver of Hepatic Inflammation Under Translational Dietary Conditions Can Be Attenuated by a Multicomponent Medicine - Mueller, Andrea M.; Kleemann, Robert; Gart, Eveline; van Duyvenvoorde, Wim; Verschuren, Lars; Caspers, Martien; Menke, Aswin; Krömmelbein, Natascha; Salic, Kanita; Burmeister, Yvonne; Seilheimer, Bernd; Morrison, Martine C. (Frontiers in Endocrinology, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) is a complex multifactorial disorder that is characterised by dysfunctional lipid metabolism and cholesterol homeostasis, and a related chronic inflammatory response. NAFLD has become the most common cause of chronic liver disease in many countries, and its prevalence continues to rise in parallel with increasing rates of obesity. Here, we evaluated the putative NAFLD-attenuating effects of a multicomponent medicine consisting of 24 ingredients: Hepar compositum (HC-24). Methods: Ldlr-/-.Leiden mice were fed a high-fat diet (HFD) with a macronutrient composition and cholesterol content comparable to human diets for 24 weeks to induce obesity-associated metabolic dysfunction, including hepatic steatosis and inflammation. HC-24 or vehicle control was administered intraperitoneally 3 times/week (1.5 ml/kg) for the last 18 weeks of the study. Histological analyses of liver and adipose tissue were combined with extensive hepatic transcriptomics analysis (next generation sequencing). Transcriptomics results were further substantiated with immunohistochemical and liver lipid analyses. Results: HFD feeding induced obesity and metabolic dysfunction that was associated with adipose tissue inflammation and increased gut permeability. In the liver, HFD-feeding resulted in a disturbance of cholesterol homeostasis and an associated inflammatory response. HC-24 did not affect body weight, metabolic risk factors, adipose tissue inflammation or gut permeability. While HC-24 did not affect total liver steatosis, there was a pronounced reduction in lobular inflammation in HC-24-treated animals, which was associated with modulation of genes involved in inflammation (e.g. neutrophil chemokine Cxcl1) and cholesterol homeostasis (i.e. predicted effect on 'cholesterol' as an upstream regulator, based on gene expression changes associated with cholesterol handling). These effects were confirmed by immunohistochemical staining of neutrophils and biochemical analysis of hepatic free cholesterol content. Intrahepatic free cholesterol levels were found to correlate significantly with the number of inflammatory aggregates in the liver, thereby providing a potential rationale for the observed anti-inflammatory effects of HC-24. Conclusions: Free cholesterol accumulates in the liver of Ldlr-/-.Leiden mice under physiologically translational dietary conditions, and this is associated with the development of hepatic inflammation. The multicomponent medicine HC-24 reduces accumulation of free cholesterol and has molecular and cellular anti-inflammatory effects in the liver.